PENERAPAN METODE YANBU’A DALAM PENINGKATAN KEFASIHAN BACA AL-QUR’AN : (Studi di TPQ Al Ihsan Desa Sanur Kaja Denpasar Bali) - Indana, Nurul; Febrianti, Anggita (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
Al-Qur'an learning today is still classical. Where in particular reading fluency and fluency is learning that is still classical in nature where learning is still centered on the teacher and students still do not play an active role in learning The success or failure of a lesson is determined by the learning method which is an integral part of the learning system. One of the methods used is the Yanbu'a method. This study aims to determine the application of the Yanbu'a method in fluency and fluency in reading the Koran. This research is a qualitative descriptive study. The results of this study indicate that in the process of implementing the learning implementation or learning method of the Yanbu'a method at TPQ Al-Ihsan, Sanur Kaja Village, Denpasar, Bali, this is in accordance with the Yanbu'a book guide. Santri are able to read the Qur'an slowly, properly and correctly according to tajwid which is called tartil. Mastery of the science of recitation, in this case students are able to pronounce letters according to the correct pronunciation or better known as makhrojul letters and in accordance with the rules.